Evaluation of condylar inclination of dentulous subjects determined by axiograph and to compare with manual programming of articulators using protrusive interocclusal record - Krishna D Prasad; Manoj Shetty; Binoj K Chandy (Wolters Kluwer Medknow Publications, 2015)
Aims: To determine the average condylar inclination using ultrasonic axiograph; to determine the average condylar inclination using protrusive interocclusal bite records; to compare whether there is any marked difference in the values obtained by these techniques. Settings and Design: This clinical study compares the mean horizontal condylar inclination of the ultrasonic axiograph (Axioquick system) and the manual programming using protrusive interocclusal records. Materials and Methods: The study was conducted on a group of 30 subjects reporting to Department of Prosthodontics. Axioquick software system of SAM III (School Articulator Munich) fully-adjustable articulator was used, and interocclusal recording of condylar inclination is the manual method used in semi-adjustable articulators using Aluwax. The condylar inclination of the articulator was adjusted and set using protrusive interocclusal record. Statistical Analysis: The horizontal condylar inclination values of both methods were collected, and the mean of right and left condylar inclination was compared using paired t-test. Results: A statistically significant difference exists between Axioquick system and the manual method of programming articulator with protrusive interocclusal records (P ≤ 0.001). Conclusions: Within the limitations of the present study, the following conclusions were drawn: The average condylar inclination by axiograph is 42.125°. The average condylar inclination by interocclusal record is 33.25°. Comparison of both values shows a difference of 8.88° ± 4.03° that showed a significant difference (P < 0.001).